Investigating aged binder mobilization and performance of RAP mixtures for surface courses. (15th February 2021) - Antunes, V.; Freire, A.C.; Neves, J.
Highlights: Homogeneous mixtures can be obtained by the use of fractionated RAP. RAP aged binder can be entirely or almost entirely mobilized when RAP is heated. RAP mixture (25%) showed a better or similar performance than reference mixture. RAP incorporation did not affect the surface characteristics. Aged RAP mixture performance envisioning good long-term behaviour. Abstract: Pavement engineering practice still deals with a set of restraints regarding the use of RAP, mainly in the case of bituminous surface courses. The main objectives of this paper are to assess: (a) the influence of the rejuvenator and the degree of aged binder mobilization on the homogeneity of bituminous mixtures; and (b) the performance and durability of bituminous mixtures for surface courses with 25% RAP. The laboratory investigation studied an AC 14 surf 35/50 considering two mixture compositions: a reference mixture with virgin constituents; and a mixture containing RAP and a rejuvenator agent. The study was focused on the mechanical and functional behaviours, as well as on the short- and long-term ageing performance of mixtures. An experimental protocol for RAP fractioning and rejuvenator addition was established to achieve a better control of the final mixture quality. The aged binder mobilization was more efficient when RAP was heated. The RAP mixture revealed a good performance in terms of permanent deformation, water sensitivity, stiffness, and fatigue. The incorporation of fractionated RAP allowed to have a mixture with good surface characteristics. Aged RAP mixture performance envisioning good long-term behaviour. Regarding the promotion of the circular economy, this investigation clearly demonstrated that mixtures with a 25% RAP incorporation can be currently used in surface courses.